Diversity and Composition of the Gut Microbiota in the Developmental Stages of the Dung Beetle Copris incertus Say (Coleoptera, Scarabaeidae) - Suárez-Moo, Pablo; Cruz-Rosales, Magdalena; Ibarra-Laclette, Enrique; Desgarennes, Damaris; Huerta, Carmen; Lamelas, Araceli (Frontiers in Microbiology, 2020)
Dung beetles are holometabolous insects that feed on herbivorous mammal dung and provide services to the ecosystem including nutrient cycling and soil fertilization. It has been suggested that organisms developing on incomplete diets such as dungs require the association with microorganisms for the synthesis and utilization of nutrients. We describe the diversity and composition of the gut-microbiota during the life cycle of the dung beetle Copris incertus using 16S rRNA gene sequencing. We found that C. incertus gut contained a broad diversity of bacterial groups (1,699 OTUs and 302 genera). The taxonomic composition varied during the beetle life cycle, with the predominance of some bacterial genera in a specific developmental stage (Mothers: Enterobacter and Serratia; Eggs: Nocardioides and Hydrigenophaga; Larval and pupal stages: Dysgonomonas and Parabacteroides; offspring: Ochrobactrum). The beta diversity evidenced similarities among developmental stages, clustering i) the adult stages (mother, male and female offsprings), ii) intermediate developmental (larvae and pupa), and iii) initial stage (egg). Microbiota differences could be attributed to dietary specialization or/and morpho-physiological factors involved in the transition from a developmental stage to the next. The predicted functional profile (PICRUSt2 analysis) for the development bacterial core of the level 3 categories, indicated grouping by developmental stage. Only 36 categories were significant in the SIMPER analysis, including the metabolic categories of amino acids and antibiotic synthesis, which were enriched in the larval and pupal stages; both categories are involved in the metamorphosis process. At the gene level, we found significant differences only in the KOs encoding functions related to nitrogen fixation, uric acid metabolism, and plant cell wall degradation for all developmental stages. Nitrogen fixation and plant cell wall degradation were enriched in the intermediate stages and uric acid metabolism was enriched in mothers. The data reported here suggested the influence of the maternal microbiota in the composition and diversity of the gut microbiota of the offspring.